2020
DOI: 10.18332/tid/121915
|View full text |Cite
|
Sign up to set email alerts
|

Active smoking is associated with severity of coronavirus disease 2019 (COVID-19 ): An update of a meta-analysis

Abstract: 1 Total (95% CI) Total events Heterogeneity:Chi z = 9.29, df = 4 (P = 0.05); I z = 57% Test for overall effect: Z = 3.00 (P = 0.003)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 9 publications
5
70
1
3
Order By: Relevance
“…One included study found active smoking to be a significant predictor of COVID-19 severity 24 , but the other four studies showed non-significant results. The pooled odds ratio for the 5 studies was found to be 1.69 (95% CI: 0.41-6.92), although this analysis has been heavily criticised for inclusion of erroneous data 25 .…”
Section: Impact Of Smoking On Disease Progressionmentioning
confidence: 96%
“…One included study found active smoking to be a significant predictor of COVID-19 severity 24 , but the other four studies showed non-significant results. The pooled odds ratio for the 5 studies was found to be 1.69 (95% CI: 0.41-6.92), although this analysis has been heavily criticised for inclusion of erroneous data 25 .…”
Section: Impact Of Smoking On Disease Progressionmentioning
confidence: 96%
“…A c c e p t e d M a n u s c r i p t increases the risk of death and infection severity in COPD [76].It has been hypothesized that the increased risk can be associated to cigarette smoke, the leading cause of COPD,which upregulates angiotensin converting enzyme 2 (ACE2), one of the most common SARS CoV-2 receptors in human lungs, most likely favoring viral dissemination [77]. However, the effects of cigarette smoke still controversial, as recent meta-analyses have questioned the relationship between SARS CoV-2 and smoking habit [78,79].…”
Section: Viruses During Copd Exacerbationsmentioning
confidence: 99%
“…Smoking has innumerable adverse health effects, and evidence points towards increased disease severity and worse outcomes in patients who smoke and experience COVID-19. [1][2][3] Also, the use of inhaled products or smokeless tobacco requires the user to put their hands near their mouth, which increases the risk of transmission of disease. 18 A better understanding of the interplay between smoking and COVID-19 can help us learn more about the pathophysiologic effect of each of them individually and identify targets for possible therapies and interventions.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Smoking has been shown to be a risk factor for disease severity and poor outcomes in coronavirus disease 2019 (COVID- 19), which is the disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). [1][2][3] It has been shown to increase the risk of the development of various types of viral infections and the incidence of complications. 4 Current smoking is associated with poorer outcomes in those with severe sepsis and septic shock 5 and the development of acute respiratory disease syndrome in hospitalized patients.…”
mentioning
confidence: 99%